The Potential of Burkholderia sp. from Zea mays Roots as Plant Growth Promoting Rhizobacteria - Mustami, Muh. Khalifah; Hafsan, Hafsan; Asri, Asri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Plant Growth-Promoting Rhizobacteria (PGPR) plays a crucial role in enhancing plant health, while Burkholderia sp. has been identified and has potential as a promising PGPR for maize plants. Recognizing the essential role of PGPR in plant health, this study explores how L-TRP addition might improve PGPR performance for better plant growth. Employing a completely randomized design, the study assesses the effects of Burkholderia sp. as PGPR on maize growth across three treatment groups: PGPR with L-TRP, PGPR without L-TRP, and a control group. The evaluation focuses on plant growth metrics, plant hormone production (auxin and gibberellin), and siderophore activity to gauge plant iron availability. Statistical analysis highlights that L-TRP supplementation notably increases auxin production in the PGPR + L-TRP group, surpassing the PGPR without L-TRP and control groups. Although both PGPR treatments elevate gibberellin levels compared to the control, auxin increase is the most significant outcome, indicating no substantial difference in gibberellin levels between the two PGPR groups. Enhanced siderophore production suggests improved iron assimilation for plants. The findings demonstrate that L-TRP supplementation with PGPR, particularly Burkholderia sp., effectively boosts maize growth, primarily through increased auxin and siderophore production. This combination presents a promising strategy for augmenting agricultural yields, especially for maize productivity, by leveraging the synergistic effects of soil microbes and nutrient supplementation.